Fractionation, Purification, and Toxicity of Methanolic Cacao Pod Husk Extract (Theobroma cacao L.) - Purnama, Agnia; Yahya, Mustanir; Ginting, Binawati; Saidi, Nurdin; Afifi, Muhammad Ridha; Maghfirah, Ruhul; Farida, Mutia; Ikhsan, Ikhsan (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2026)
Cacao (Theobroma cacao, L.) is a plantation product that has good prospects, but its processing produces a by-product in the form of cacao pod husks that have not been optimally utilized. This study aims to analyze the toxicity of methanol extracts, fractions, and subfractions of cacao pod husks using the Brine shrimp lethality test (BSLT) assay, and to purify active compounds using gravity column chromatography and thin-layer chromatography (TLC). The fractionation process of the methanol extract produced 5 fractions and 4 subfractions. The results of the toxicity analysis showed that the TCM 2 fraction and the TCM 2.1 subfraction had the highest toxicity, with IC₅₀ values of 38.68 ppm and 28.85 ppm, respectively. Further purification process produced a single isolate identified as a terpenoid compound. The results of this study indicate that cacao pod husks have the potential to serve as a natural source of toxicity and can be developed for use in the pharmaceutical field.